2016
DOI: 10.1002/iub.1497
|View full text |Cite
|
Sign up to set email alerts
|

Where have all the inosines gone? Conflicting evidence for A‐to‐I editing of the anticodon of higher eukaryotic questions the dogma of a universal wobble‐mediated decoding of CGN codons

Abstract: Codon-anticodon recognition between triplets of an mRNA and a specific tRNA is the key element in the translation of the genetic code. In general, the precision of this process is dominated by a strict Watson-Crick base-pairing scheme. However, the degeneracy of the genetic code led Crick to propose the Wobble Hypothesis, permitting a less restraining interaction with the third base of the codon and involving the participation of inosine for decoding C-ending codons. The concept that the anticodon base A34 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…For example, while ∼90% of sequencing reads mapping to tRNA Val AAC reflected the presence of I34, <2% of reads mapping to tRNA Arg ACG evidenced I34 modification on this tRNA . This is consistent with other reports that describe the difficulty of detecting I34 on tRNA Arg ACG in higher eukaryotes by RT-based methods …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…For example, while ∼90% of sequencing reads mapping to tRNA Val AAC reflected the presence of I34, <2% of reads mapping to tRNA Arg ACG evidenced I34 modification on this tRNA . This is consistent with other reports that describe the difficulty of detecting I34 on tRNA Arg ACG in higher eukaryotes by RT-based methods …”
Section: Discussionsupporting
confidence: 91%
“…I34 is an essential posttranscriptional tRNA modification of biomedical importance that played an important role in the evolution of eukaryotic genomes and proteomes , Currently available methods for detecting I34, such as RT-based sequencing strategies, can be limited by technical artifacts that compromise their interpretation (Figure ). We have previously shown that deep sequencing of tRNAs can be used to detect I34 on precursor tRNAs in vivo , but the efficiency of I34 detection varied considerably among different I34-tRNA species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These analyses show that detected peptides are more likely translated according to the mitochondrial genetic code than according to the nuclear genetic code. Note that translation, within the mitochondrion, according to the nuclear code is possible: it potentially depends for some codons upon the presence of cytosolic tRNAs, which could be occasionally imported in mitochondria [21] , [32] , [39] , [44] , [75] , [76] , [78] , [112] , [114] . However, this rationale is not symmetric: cytosolic translation according to the mitochondrial genetic code is much less probable than the opposite, so that nuclear origins are not compatible with the results obtained.…”
Section: Discussionmentioning
confidence: 99%